R&D in Cleaner Technology and International Trade - Slim Ben Youssef (Fondazione Eni Enrico Mattei (FEEM), 2004)
We consider a dynamic three-stage game played by two regulator-firm hierarchies to capture the scale and technological effects of opening markets to international trade. Each firm produces one good sold on the market. Firms can invest in R&D in order to lower their fixed emission/output ratio and are regulated with costly public funds. We take the context of sufficiently high market sizes and investment cost parameters. Opening markets to international trade yields more investment in R&D, more production and a lower emission ratio. When the market size is low enough and the investment cost parameter is high enough, pollution in common market is higher than in autarky. International trade reduces the social welfare.
Keywords: D62; F12; O32; 330; R&D; Cleaner technology; Common market; Social welfare; Umweltbelastung; Umwelttechnik; Industrieforschung; Handelsliberalisierung; Wohlfahrtsanalyse; Zwei-Länder-Modell; Theorie; Nichtkooperatives Spiel